Kinome scale profiling of venom effects on cancer cells reveals potential new venom activities. (15th October 2020) - McCullough, Danielle; Atofanei, Cristina; Knight, Emily; Trim, Steven A.; Trim, Carol M.
Abstract: The search for novel and relevant cancer therapeutics is continuous and ongoing. Cancer adaptations, resulting in therapeutic treatment failures, fuel this continuous necessity for new drugs to novel targets. Recently, researchers have started to investigate the effect of venoms and venom components on different types of cancer, investigating their mechanisms of action. Receptor tyrosine kinases (RTKs) comprise a family of highly conserved and functionally important druggable targets for cancer therapy. This research exploits the novelty of complex venom mixtures to affect phosphorylation of the epidermal growth factor receptor (EGFR) and related RTK family members, dually identifying new activities and unexplored avenues for future cancer and venom research. Six whole venoms from diverse species taxa, were evaluated for their ability to illicit changes in the phosphorylated expression of a panel of 49 commonly expressed RTKs. The triple negative breast cancer cell line MDA-MB-468 was treated with optimised venom doses, pre-determined by SDS PAGE and Western blot analysis. The phosphorylated expression levels of 49 RTKs in response to the venoms were assessed with the use of Human Phospho-RTK Arrays and analysed using ImageLab 5.2.1 analysis software (BioRad). Inhibition of EGFR phosphorylation occurred with treatment of venom from Acanthoscurria geniculata (Theraphosidae), Heterometrus swammerdami (Scorpionidae), Crotalus durissus vegrandis (Crotalidae) and Naja naja (Elapidae) . Western green mamba Dendroaspis viridis venom increased EGFR phosphorylation. Eph, HGFR and HER were the most affected receptor families by venoms. Whilst the importance of these changes in terms of effect on MDA-MB-468 cells' long-term viability and functionality are still unclear, the findings present exciting opportunities for further investigation as potential drug targets in cancer and as tools to understand better how these pathways interact. Highlights: Kinome profiling demonstrates venom effects on receptor tyrosine kinase phosphorylation. Theraphosidae, Scorpionidae, Crotalidae and Elapidae venoms inhibit phosphorylation of the epidermal growth factor receptor. Venom components can be used as tools to characterise poorly known cancer pathways. Phosphorylation of the putative anti-cancer target Ephrin A6 is downregulated by Theraphosidae and Elapidae venom.